Senecio namibensis (Asteraceae: Senecioneae), a new species from Namibia - Swanepoel, Wessel; Becker, Rolf; de Cauwer, Vera; van Wyk, Abraham E. (Phytotaxa, 2022)
Senecio namibensis is described as a new species known only from the northern part of the Namib Desert in northwestern Namibia. It is a range-restricted species near-endemic to the Kaokoveld Centre of Endemism. These dwarf shrubs grow on rocky outcrops under harsh desert conditions. Diagnostic characters for Senecio namibensis include the annual or perennial habit, succulent leaves, and radiate capitula with 3–6 yellow ray florets. A comparison of some of the more prominent morphological features to differentiate between S. namibensis and its possible nearest relatives, S. englerianus and S. flavus, is provided. All three species have superficially similar looking succulent leaves, but an obvious difference is that the capitula in S. englerianus are discoid and in S. flavus disciform or obscurely radiate. Based on IUCN Red List categories and criteria, a conservation assessment of Least Concern (LC) is recommended for the new species.